A study on customer satisfaction towards seminar package offered by Hotel Seri Malaysia Sungai Petani / Azlina Ahmad - Ahmad, Azlina (1999)
This study will focus on measuring customer satisfaction towards seminar package offered by Hotel Seri Malaysia Sungai Petani where it will help the hotel to identify customer level of satisfaction in order to improve or at least maintain it through recommendation suggested by the researcher. This study was conducted at Seri Malaysia Sungai Petani where the focused respondent were the customer who using the seminar package. The problem statement of this research is to know the seminar package performance, the level of customer satisfaction and promotional strategy in the hotel perceive by their customer. From the finding, the result shows that the overall customer satisfaction on the seminar package is at moderate satisfied level. It means that the customer were satisfied with the service provided during the seminar but it not enough to increase the sales. So the